Layered Li1.3Mn0.58Ni0.12Co0.11O2+δ Cathode Material for Lithium‐Ion Batteries with High Reversible Capacity. Issue 12 (11th August 2016) - Deng, Ya‐Ping; Fu, Fang; Wu, Zhen‐Guo; Zhang, Tao; Yin, Zu‐Wei; Zhang, Shao‐Jian; Li, Jun‐Tao; Huang, Ling; Sun, Shi‐Gang
Abstract: Layered Li1.3 Mn0.58 Ni0.12 Co0.11 O2+ δ, a solid solution of 0.53 Li2 MnO3 ⋅0.47 LiMn0.4 Ni0.3 Co0.3 O2, has been successfully synthesized by using an improved solvothermal strategy and used as the cathode material of a Li‐ion battery. The pure phase of the layered structure is characterized by using X‐ray diffraction and Raman spectroscopy. Electrochemical tests demonstrate that as‐synthesized layered Li1.3 Mn0.58 Ni0.12 Co0.11 O2+ δ exhibits high discharge capacities of 349.4, 322.4, 304.6, and 291.7 mAh g −1 at 0.1, 0.2, 0.5, and 1 C rates, respectively. Such high reversible capacities could be ascribed to the enrichment of oxygen in the materials, which was evidenced clearly by a potential plateau below 3.0 V in the discharge process and originated form the electrochemical oxygen reduction. Abstract : Layer cake : A layered Li1.3 Mn0.58 Ni0.12 Co0.11 O2+ δ cathode material for Li‐ion batteries is successfully synthesized through an improved solvothermal route. Electrochemical tests demonstrate that the as‐synthesized Li‐rich material can deliver high initial discharge capacities of 349.4, 322.4, 304.6, and 291.7 mAh g −1 at 0.1, 0.2, 0.5, and 1 C, respectively, between 2.0 and 4.8 V.